PENGARUH SANKSI PAJAK, KEPERCAYAAN PADA PEMERINTAH DAN HUKUM, PELAYANAN FISKUS TERHADAP KEPATUHAN PBB (Survei pada Wajib Pajak PBB di Desa Kemasan Kecamatan Sawit Kabupaten Boyolali) - Santoso, Wahyu Budi; Harimurti, Fadjar; Sunarti, Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The intention of this deepening is to analyze the meaning of the influence of tax sanctions, trust in the government and law, special services, in addition to understanding among the ruling variables that have an impact on the mandatory compliance of the PBB in the Village of Kemasan. This type of exploration is a survey on the PBB mandatory in the Village of Kemasan. all the PBB mandatory registered in the Kemasan Village is the population in this study. Random sampling became a sampling technique in this study for 100 PBB taxpayers. Data collection techniques using a questionnaire statement. Data analysis methods required, Classic Assumption Test, Multiple Linear Regression Analysis, t Test, F Test (Model Accuracy), Test (R2). The results of these observations indicate that tax sanctions, trust in the government and law, the tax authorities services will impact on PBB compliance in the Village of Kemasan. The result of the coefficient of determination (R2) is 0.520, this means that the contribution or effect supported by the variable tax sanctions, trust in the government and the law, special services to PBB revenue is 52.0% while the remaining 48.0% is influenced by variables outside research studied.